Designing Data Warehouse at the Impatient and Outpatient (Case Study: Sanglah Hospital) - Andreyana, Putu Veda; Widya, Putu Angelina; Suartika, Made (International Journal of Engineering and Emerging Technology; Vol 2 No 1 (2017): January - June, 2017)
The growth of patient data increasing the hospital resulted in even harder to compile data and analyze the data manually, so it takes a data warehouse that can perform this task automatically. The design of the data warehouse Sanglah hospital aims to build a data warehouse that can store data in structured and easier to analyze the data to make a decision. Design methods Fact Constellation Schema and method used is a Nine-step methodology consisting of nine stages, namely the Electoral Process, Selection of Grain, identification and adjustment of the dimensions, the Electoral Facts, Storage pre-calculation in the fact table, Ensuring the dimension tables, the Electoral duration database, Track changes of dimensions is slowly, prioritization and query model. Designing Data Warehouse Sanglah Hospital helpful enough for data processing in large enough quantities, so expect the needs and information about the patient can be met. Data warehouse Sanglah Hospital can be used to analyze patient data in order to get information on the number of patients of various dimensions